Conservation Management of the Banggai Cardinalfish in the Banggai Kepulauan District MPA- A Genetic Approach - Ndobe, Samliok; Setyohadi, Daduk; Herawati, Endang Yuli; _, Soemarno; Moore, Abigail (Journal of Indonesian Coral Reefs, 2011)
The Banggai cardinalfish (Pterapohon kauderni, Koumans 1933),often refered to as BCF, is a restricted range coral reef associated fish endemic to shallow waters (0-5m) arround the Banggai Archipelago, Indonesia. Listed as EndangeredÂ un the IUCN Red-List. In 2007 a national BCF Action Plan was developed , and a Distrct MPA was established by decree of the BanggaiÂ  Kepulauan District Head, consisting of a network of 10 islands. For 2 of these P. Kauderni conservation in the main management target. We reviewed available phylogenic, genetic and biogeographical data, and examined the MPA network from the viepoint of P. Kauderni genetic diversity conservation. With no pelagic phase and high fidelity, the Banggai cardinalfish population exhibits a level of genetic structure unusual in a marine fish. Several genetically distinct sub populations have been identified. It was concluded that management units should be basedÂ  on genetically detrmined sub-populations (stocks). Critical knowledge gaps and several research pririties were identified. In particular , we conclude that a researh programme is necesary for the identification and characterisation of these genetically determined units from biological (including genetic), ecological (e.g. habitat/micro-habitat) and socio-economic (including fishing ground) aspects. We propose to provide management support through the use of the spatial analysis tool MARXAN combined with a GIS database to produce science-based zoning options with management units/targets based on genetic population structure.